MON-174 Type II Diabetics Decrease Hypertensive Medication and Improve Blood Pressure in 18 Days - Michel, Rebecca (J Endocr Soc, 2019)
Diabetes and hypertension are often co-morbid conditions leading to adverse health outcomes. Since diabetes and hypertension share common risk factors such as obesity, lifestyle interventions may address the cause of these diseases. An intensive 18-day medical residential lifestyle intervention and educational program was used to measure the impact of lifestyle interventions on type II diabetic’s systolic blood pressure (SBP), antihypertensive medication use, and weight loss. This residential lifestyle program in Weimar, CA uses whole foods plant-based nutrition, outdoor exercise, adequate water consumption, self-control, sleep hygiene, and spiritual components with the help of chaplaincy (dealing with anger, forgiving others, etc). Every patient received cooking classes and multiple health education lectures. A board certified physicians monitored progress adjusting medication and dosages during the program. Blood pressure was taken multiple times during the intervention, every patient received a before and after stress test and blood analysis. Diabetic SBP, antihypertensive medications, and weight loss were measured at baseline and at the end. From n=2081 patients in a span of 11 year, n=668 patients were retrospectively used in this study which had the diagnosis of diabetes type II and had complete files, from that group n=110 were taking blood pressure medications. Among patients taking blood pressure medications, weight decreased from an average of 180.2±41.59lbs to 174.9±38.79lbs (p<0.01; n=110) at the end. There was significant improvement on SBP after the program in participants with diabetes by 3.07mmHg decrease (p<0.01; n=668). Among diabetic individuals not taking blood pressure medications the mean SBP improvement was 3.16mmHg decrease (p<0.01; n=558). Diabetic taking blood pressure medications had a modest but not significant improvement in their SBP -2.61mmHg (p<0.06; n=110). From n=110 only n=94 had complete documentation of the medication dosage before and after. There was over two-thirds reduction in blood pressure medication dosages (-76.5%±49.5%; n=94). At baseline n=94 people who were taking blood pressure medications 86.2% (n=81) completely went off medications by the end, 12.8% stayed on the same dosage of medications (n=12), and 1% received a higher dosage of medication (n=1) at the end of the intervention. This interventional-educational lifestyle program effectively lowered SBP in diabetic subjects while markedly reducing antihypertension medication usage. Benefits of a healthy lifestyle were not limited to blood pressure control in diabetic patients, but also include weight loss, improved glycemic control, lower lipid profile, decrease coronary artery disease and stroke risk index. Clinicians should promote healthier lifestyle choices to all patients at risk for lifestyle related diseases.